# Solve for n 5(3n-7)-4=5(n-4)+61

5(3n-7)-4=5(n-4)+61
Simplify 5(3n-7)-4.
Simplify each term.
Apply the distributive property.
5(3n)+5⋅-7-4=5(n-4)+61
Multiply 3 by 5.
15n+5⋅-7-4=5(n-4)+61
Multiply 5 by -7.
15n-35-4=5(n-4)+61
15n-35-4=5(n-4)+61
Subtract 4 from -35.
15n-39=5(n-4)+61
15n-39=5(n-4)+61
Simplify 5(n-4)+61.
Simplify each term.
Apply the distributive property.
15n-39=5n+5⋅-4+61
Multiply 5 by -4.
15n-39=5n-20+61
15n-39=5n-20+61
Add -20 and 61.
15n-39=5n+41
15n-39=5n+41
Move all terms containing n to the left side of the equation.
Subtract 5n from both sides of the equation.
15n-39-5n=41
Subtract 5n from 15n.
10n-39=41
10n-39=41
Move all terms not containing n to the right side of the equation.
Add 39 to both sides of the equation.
10n=41+39
Add 41 and 39.
10n=80
10n=80
Divide each term by 10 and simplify.
Divide each term in 10n=80 by 10.
10n10=8010
Cancel the common factor of 10.
Cancel the common factor.
10n10=8010
Divide n by 1.
n=8010
n=8010
Divide 80 by 10.
n=8
n=8
Solve for n 5(3n-7)-4=5(n-4)+61

## Our Professionals

### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top